(untitled) (International Journal of Environmental Sciences, 2025)
The criminalization of ecocide has gained global focus as environmental degradation approaches catastrophic levels. This research examines the need to recognise ecocide—defined as severe, prevalent, or long-term environmental harm—as an international crime under the Rome Statute. It analyses the legal, ethical, and geopolitical implications of creating ecocide as the fifth international crime, together with genocide, war crimes, crimes against humanity, and belligerence. Drawing from secondary data sources, comprising case studies, treaties, and expert legal opinions, the research emphasises gaps in current international environmental law, such as weak implementation and state dominion barriers. By examining key incidents like the Deepwater Horizon spill and Amazon deforestation, the research calls for robust legal frameworks to grasp states and corporate actors accountable. The study endorses the inclusion of ecocide within the International Criminal Court’s jurisdiction, highlighting the urgency of legal deterrents to prevent irreversible ecological destruction. It determines that acknowledging ecocide as a crime is essential to ensuring global environmental justice and protecting the planet for future generations.